2019
DOI: 10.1108/caer-12-2018-0243
|View full text |Cite
|
Sign up to set email alerts
|

Targeted poverty reduction under new structure

Abstract: Purpose The purpose of this paper is to investigate the impact of social capital on the mental health of older adults in rural China. The authors also examine potential heterogeneous effects and two possible pathways from social capital increase to mental health improvement. Design/methodology/approach Based on a panel data of China Health and Retirement Longitudinal Study, this paper employs a fixed effect model to examine the impact of social capital on health. A two-stage instrumental variable approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Due to the lack of data, a self-reported health variable can be used to measure health status in the present study. However, numerous studies have confirmed the validity and rationality of such self-reported health variables [8,13,14,31,32,33,34,35,36,37]. Second, this study examined only the income and psychological effects, but neglected other potential explanations at the societal or community level.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Due to the lack of data, a self-reported health variable can be used to measure health status in the present study. However, numerous studies have confirmed the validity and rationality of such self-reported health variables [8,13,14,31,32,33,34,35,36,37]. Second, this study examined only the income and psychological effects, but neglected other potential explanations at the societal or community level.…”
Section: Discussionmentioning
confidence: 98%
“…[6,7,8,9,10,11,12,13,14]. At the micro level, age, gender, educational level, marital status, environmental quality, water quality, sanitation level, income level and religious beliefs all have an impact on the health of rural residents [11,12,13,14,15,16,17]. At the macro level, health expenditure in rural areas, accessibility of medical services and outflow of rural labor force are closely related to the health of the rural residents [18,19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the inclusion relation between γ δ Φ(A) and other eigenvalue inclusion sets is discussed. As an application, a new criterion for identifying nonsingular tensors [14,17] is provided. In order to show the superiority of the new results, numerical examples are given in Section 3.…”
mentioning
confidence: 99%